Characterization of laser wakefield acceleration efficiency with octave spanning near-IR spectrum measurements - M. J. V. Streeter; Y. Ma; B. Kettle; S. J. D. Dann; E. Gerstmayr; F. Albert; N. Bourgeois; S. Cipiccia; J. M. Cole; I. Gallardo González; A. E. Hussein; D. A. Jaroszynski; et al. (Physical Review Accelerators and Beams, 2022)
We report on experimental measurements of energy transfer efficiencies in a GeV-class laser wakefield accelerator. Both the transfer of energy from the laser to the plasma wakefield and from the plasma to the accelerated electron beam was diagnosed by simultaneous measurement of the deceleration of laser photons and the acceleration of electrons as a function of plasma length. The extraction efficiency, which we define as the ratio of the energy gained by the electron beam to the energy lost by the self-guided laser mode, was maximized at 19±3% by tuning the plasma density and length. The additional information provided by the octave-spanning laser spectrum measurement allows for independent optimization of the plasma efficiency terms, which is required for the key goal of improving the overall efficiency of laser wakefield accelerators.